ANALISIS POLITIK HUKUM PENGATURAN PRESIDENTIAL THRESHOLD BERDASARKAN UNDANG-UNDANG DASAR NEGARA REPUBLIK INDONESIA TAHUN 1945 - Ridho, Havid; Haryono, Dodi; Junaidi, Junaidi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2024)
Article 222 No. 7 of 2017 concerning General Elections as an entry point forpolitical cartels, both the requirements for presidential candidates and vice presidentialcandidates and the procedures for presidential elections in the 1945 Constitution do notregulate the requirement sthreshold and the 1945 Constitution does not delegate laws toregulate condition shreshold and Article 222 does not provide legal certainty becauseneither new parties nor old parties that do not have 20% of the seats or 25% of the validnational vote can nominate presidential and vice presidential candidates.The purpose of writing this thesis is: first, to understand the political and legalregulations Presidential Threshold in the election of President and Vice President asregulated in Law Number 7 of 2017. Second, to find out about the arrangementsPresidential Trheshold In the General Election, it is in accordance with the Political andLegal Analysis of the 1945 Constitution. Third, to find out the Analysis of Legal PoliticalConformity Presidential Trheshold in Law Number 7 of 2017 Linked to the 1945Constitution. The research method in this thesis uses normative juridical research, namelyresearch that focuses on examining the application of rules or norms in positive law. Thedata source used is the data sourcefirst, seconds andtertiary, The data collection methodused in this research is firstly literature study, which is a technique for obtainingsecondary data through documents related to the problem, objectives and benefits of theresearch, then after the data is collected it is then analyzed to draw conclusions.Based on the research results, the first conclusion can be drawn that political legaldetermination Presidential Threshold in the election of the president and vice presidentregulated in law no. 7 of 2017 in the Law of the Republic of Indonesia of 1945 presentedas a form of strengthening the presidential system, and requiring a government thatisbalanced and mutually controlled Second Arrangement presidential threshold in theElection Law, this actually creates a contradiction or incongruity with the spirit of theconstitution, which has actually opened up the widest possible space for political partiesparticipating in the election to nominate presidential and vice presidential candidateswithout being limited by the threshold for obtaining votes or seats in parliament.Keywords: Election, presidential threshold, 1945 Constitution